Pola Konsumsi Pangan Nelayan Bajo di Desa Banu – Banua Jaya Kecamatan Kulisusu Kabupaten Buton Utara - Ifan, Ifan; Mukhtar, Mukhtar; Zani, Munirwan (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2018)
This study aims to identify and analyze: (1) The pattern of food consumption of households of fishermen Bajo in the village of Banu-Banua Jaya subdistrict Kulisusu North Buton, (2) The type of food consumed by households fishermen Bajo in the village of Banu-BANUA Jaya subdistrict Kulisusu District North Buton as a source of carbohydrates, protein and vitamins and (3) the relationship between the level of income by the number of types of food sources of carbohydrates, protein and vitamins that are consumed by households in the village of Bajo fishermen Banu-BANUA Jaya subdistrict Kulisusu North Buton. This research was conducted in November and December 2016. The samples were done by simple random method by taking a sample of 15% of the total population of 207 families, as many as 31 people. The data was processed using descriptive analysis and Pearson correlation analysis. The results showed that: (1) Household Bajo fishermen in the village of Banu-BANUA Jaya have food consumption patterns that vary at the time of breakfast, lunch, supper, dinner and midnight. Foodstuffs consumed include: rice, fish, vegetables, eggs, instant noodle, and pastries, (2) Type of food sources of carbohydrates are consumed fisherman Bajo is rice, instant noodle, cake, cassava and kansoami then sources of protein are fish and eggs , while the source of the vitamin only from vegetables and banana, (3) revenues have a strong enough relationship and significant with the number of types of food sources of carbohydrates and protein, high and low income means followed by a great variety of food sources of carbohydrates and protein consumed. While the types of food sources of vitamin ties are weak and insignificant and minerals have no relation to income, meaning that high and low income is not followed by a great variety of food sources of vitamins and minerals are consumed.